2018
DOI: 10.1086/698859
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation and Green Skills: An Empirical Exploration

Abstract: This paper provides new evidence on the workplace skills most relevant in the transition toward environmentally sustainable economies. Using a novel datadriven methodology, we identify two main sets of green skills, namely, engineering skills for the design and production of technology, and managerial skills for implementing and monitoring environmental organizational practices. Exploiting exogenous geographical variation in regulatory stringency, we also evaluate the effect of environmental regulation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
178
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(202 citation statements)
references
References 42 publications
(48 reference statements)
17
178
0
7
Order By: Relevance
“…They generally found modest differences but also a bias towards higher skills for green jobs (see also Bowen et al, 2018). Vona et al (2018) was the first paper to provide a direct test of the effect of recent amendments to the Clean Air Act on skill demand in US regions over the period 2006-2014. Extending the nuanced results of Consoli et al (2016) obtained using standard skill measures, they also used O * NET to identify the skills that are significantly different between green jobs and other jobs.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…They generally found modest differences but also a bias towards higher skills for green jobs (see also Bowen et al, 2018). Vona et al (2018) was the first paper to provide a direct test of the effect of recent amendments to the Clean Air Act on skill demand in US regions over the period 2006-2014. Extending the nuanced results of Consoli et al (2016) obtained using standard skill measures, they also used O * NET to identify the skills that are significantly different between green jobs and other jobs.…”
Section: Related Literaturementioning
confidence: 99%
“…We focus our analysis on four occupational groups: managers (ISCO 1), professionals (ISCO 2), technicians (ISCO 3) and manual workers (ISCO 7, 8 and 9). The paper by Vona et al (2018), which empirically identifies the skills relevant for green and brown jobs, motivates the separate inclusion of professionals, managers and technicians. Engineering and design skills emerge as the most important skills for both the green and polluting sectors.…”
Section: Data and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the reform and opening up of China's economy in December 1978, the environmental problems caused by the country's extensive economic growth are attracting increasing global attention [1][2][3]. The signing of the International Framework Convention on Climate Change and the finalization of the Paris Agreement have shown that governments, while striving to increase the level of economic development, must also consider environmental protection [4][5][6]. Given the nature of environmental public goods, property rights are difficult to define, and the problem of negative externalization cannot be solved completely by relying solely on the market mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant empirical contributions emerged from the use of the BLS GGS data, and from debates regarding the definition and measurement of green economic activities in the US. This includes research where the BLS data has been linked to the O*NET database to enable the task-based identification of green jobs (Vona et al, 2018a(Vona et al, , 2018b. This approach, and the relationship of the BLS data to NAICS codes, permits analyses of the distribution of green jobs that are disaggregated by location and by education-level.…”
Section: Previous Green Economy Measurement By the Us Federal Governmentmentioning
confidence: 99%